The impact of project-based learning on EFL learners’ learning motivation and academic performance: an empirical study in a Chinese rural school - Panpan Yang; Sirui Chen; Wenlan Zhang; Jiawei Chen (Humanities & Social Sciences Communications)
Abstract Project-based learning (PBL) as an instructional method has been adopted across various academic disciplines, including foreign language education. While existing research has demonstrated the significant efficacy of PBL in enhancing students’ foreign language acquisition, investigations into its implementation and effectiveness within rural education settings remain notably scarce. This study adopted a mixed method design to conduct an 8-week pedagogical intervention, analyzing the effectiveness of PBL on EFL learners’ learning motivation and academic performance in a Chinese rural junior middle school. The quantitative results showed that the projected-based language learning (PBLL) enhanced EFL learners’ learning motivation, whereas its impact on academic achievement tests yielded limited effects. The qualitative data indicated that EFL learners showed greater interest in PBLL instruction. The findings suggest that PBLL can serve as an effective pedagogical approach to enhance rural EFL learners’ learning motivation, contextual writing skills, and alignment between instruction and standardized assessment.